2018
DOI: 10.3390/foods7100173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Processed Chickpea Flour Incorporation into “Mankoushe” on Appetite Hormones and Scores

Abstract: Recently, there has been an increasing interest in integrating pulse flours into pastries and baked products to improve their nutritional and health benefits. “Mankoushe,” a popular Lebanese pastry made up of refined wheat flour was enriched with chickpea flour that is of better nutritional value, and its postprandial glycemia, insulinemia, lipidemia and appetite measures were monitored. A randomized cross-over study was performed on sixteen healthy Lebanese females, age (years): 22.90 ± 3.00, and BMI (kg/m2):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A previous trial investigating the impact of incorporating chickpea flour in flat breads reported no effects on GLP-1 levels although significantly higher levels of ghrelin were measured as a result of the intervention. 48 However, the incorporated chickpea flour only amounted to 30% in the intervention meals, accounting for consistency in both glucose and insulin responses. 48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous trial investigating the impact of incorporating chickpea flour in flat breads reported no effects on GLP-1 levels although significantly higher levels of ghrelin were measured as a result of the intervention. 48 However, the incorporated chickpea flour only amounted to 30% in the intervention meals, accounting for consistency in both glucose and insulin responses. 48…”
Section: Discussionmentioning
confidence: 99%
“…48 However, the incorporated chickpea flour only amounted to 30% in the intervention meals, accounting for consistency in both glucose and insulin responses. 48…”
Section: Discussionmentioning
confidence: 99%
“…In alignment with blood glucose, pulse intake favorably affected post-prandial insulin levels with a larger effect in T2D population where reduction in PPGR was greater. There were large variations between RCTs with regards to characteristics of participants such as mean age (22-66 y) and BMI (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), that might influence insulin secretion and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of randomized controlled trials have assessed the effect of pulse intake on acute post-prandial and longterm glucose response [14][15][16][17][18][19][20][21][22][23]. The studies differed in the type of pulses used, processing, doses and control group, and in different volunteer profiles [6,[24][25][26][27][28][29][30][31][32][33]. The study outcomes vary considerably with low quality of evidence and, therefore, the true effect size of pulse intake on measures of glycemic handling remains unclear [34].…”
Section: Introductionmentioning
confidence: 99%
“…Body composition measurements were obtained using the GAIA 359 PLUS device, which has been employed in several research studies due to its proven reproducibility and reliability in the assessment of body composition [16][17][18] . The device works on the principle of measuring the resistance of the human body when alternating current is passed through it.…”
Section: Methodsmentioning
confidence: 99%